2017
DOI: 10.1038/nature22027
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Corrigendum: The histone H4 lysine 16 acetyltransferase hMOF regulates the outcome of autophagy

Abstract: In this Letter, during the preparation of Figs 1b and 3b, and Supplementary Figs 3c and 10a, the digital western blot scans were processed to remove irrelevant lanes from single-blot images. Although all excisions/mergers originated from the same gel, these figure constructions should have been explicitly pointed out. We now include the unprocessed scans of the corresponding blots as Supplementary Information to this Corrigendum. In addition, the original GRO-seq data have been uploaded at ArrayExpress with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…Having established that KANSL1-deficiency results in increased oxidative stress causing elevated autophagosome formation and reduced synaptic activity, we wondered what causes the autophagosome accumulation in KANSL1-deficient cells. Increased autophagic flux is known to induce a regulatory feedback-loop in which induction of autophagy is coupled to a reduction in H4K16ac through downregulation of hMOF in MEF cells [15]. However, we did not find a reduction in H4K16ac in KANSL1-deficient cells at the basal level.…”
Section: Impaired Feedback-loop and Decreased Lysosomal Activity In Kdvs Cellscontrasting
confidence: 86%
See 3 more Smart Citations
“…Having established that KANSL1-deficiency results in increased oxidative stress causing elevated autophagosome formation and reduced synaptic activity, we wondered what causes the autophagosome accumulation in KANSL1-deficient cells. Increased autophagic flux is known to induce a regulatory feedback-loop in which induction of autophagy is coupled to a reduction in H4K16ac through downregulation of hMOF in MEF cells [15]. However, we did not find a reduction in H4K16ac in KANSL1-deficient cells at the basal level.…”
Section: Impaired Feedback-loop and Decreased Lysosomal Activity In Kdvs Cellscontrasting
confidence: 86%
“…Gene ontology analysis identified changed promoter activation of genes within oxidoreductase and mitochondria pathways [22], suggesting increased oxidative stress in KdVS mice. We performed qPCRs for a set of H4K16ac regulated ATG genes [15], that showed differentially activated promoters in the KdVS mouse model. We identified SOD1 (superoxide dismutase 1), an antioxidant enzyme that reduces superoxide, to be about one third lower expressed in KdVS patient derived iPSCs (Figure S2A).…”
Section: Autophagosome Accumulation Is Caused By Increased Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Total expression of caspase 3 changed inapparently, but the p17-caspase 3 was obviously up-regulated. However, studies have shown that MOF also plays an important role in autophagy ( Füllgrabe et al, 2017 ), so further research is needed on the effects of excluding autophagy in apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%